28 GHz Patch Antenna Array with Reduced Mutual Coupling for 5G Communications Systems - Mwang ' amba, Rahabu F.; Iddi, Hashimu U. (Tanzania Journal of Engineering and Technology, 2022)
A 28 GHz patch antenna array with reduced mutual coupling for 5G communication systems is presented in this paper. Two elements antenna array was simulated with a periodic boundary to represent an infinity array. The antenna array is attached with a pair of the coupled directional coupler with a coupling value of -3.47 dB, and transmission lengths of 3.40 mm and 7.62 mm depending on the antenna array's magnitude and phase coefficient were designed and simulated. A reduced mutual coupling of -31.86 dB compared to -10.75 dB for an array without a decoupling network was observed. The wide scanning angle of ±180o was also achieved. These results were obtained under smaller antenna elements interspacing of 0.43Î»0. Moreover, the proposed antenna array design achieved a 3.32 GHz enhanced fractional bandwidth which is 11.8%. Generally, this work found that the combinatorial advantages of using the gap coupled insert feed technique and employing a pair of directional couplers develop the patch antenna array design with better performance. Keywords: Patch Antenna Array, Mutual Coupling, Scanning Angle, 5G, Directional Coupler, and Gap Coupled Insert Feed.